Synthesis and preclinical evaluation of gastrin releasing peptide receptor antagonist [18F]MeTz-PEG2-RM26 for positron emission tomography - Panagiotis Kanellopoulos; Fanny Lundmark; Ayman Abouzayed; Lorenzo Jacopo Ilic Balestri; Esther Olaniran Håkansson; Karim Obeid; Luke R. Odell; Vladimir Tolmachev; Ulrika Rosenström; Jonas Eriksson; Anna Orlova (EJNMMI Radiopharmacy and Chemistry)
Abstract Background The gastrin-releasing peptide receptor (GRPR) is overexpressed in the majority of primary prostate cancer lesions, with persistent expression in lymph nodes and bone metastases, making it a legitimate molecular target for diagnostic imaging and staging. This study presents the synthesis and preclinical evaluation of [18F]MeTz-PEG2-RM26, a GRPR antagonist which utilises the Inverse Electron Demand Diels-Alder (IEDDA) reaction for 18F-labelling. This click-chemistry approach allows for site-specific incorporation of fluorine-18 under mild conditions, preserving the peptide’s structural integrity and biological activity. Receptor specificity and affinity of [18F]MeTz-PEG2-RM26 were evaluated in vitro using GRPR-expressing PC-3 cells. Furthermore, the biodistribution profile of [18F]MeTz-PEG2-RM26 was assessed in NMRI mice and its tumour-targeting capability was investigated in mice bearing PC-3 xenografts. Results The labelling of TCO-PEG2-RM26 precursor involved three steps: (1) synthesis of an 18F-labelled activated ester on a quaternary methyl ammonium (QMA) cartridge, (2) conjugation of the labelled ester to a tetrazine amine, and (3) attachment to TCO-PEG2-RM26 via an IEDDA click reaction. This production method of [18F]MeTz-PEG2-RM26 afforded a high apparent molar activity of 3.5–4.3 GBq/µmol and radiochemical purity exceeding 98%, with 43–70 MBq activity incorporation, while the entire synthesis was completed within 75 min. Both in vitro and in vivo studies confirmed the specific binding of [18F]MeTz-PEG2-RM26 to GRPR, with a significant reduction in activity uptake observed upon receptor saturation. The radioligand exhibited rapid blood clearance and minimal bone uptake, confirming the stability of the fluorine-carbon bond. However, high hepatic uptake (12–13% IA/g at 1 h post-injection) indicated predominant hepatobiliary excretion. Receptor-mediated uptake was observed in the tumours and pancreatic tissue, although the overall activity uptake in tumours was low, likely due to the rapid hepatobiliary clearance of [18F]MeTz-PEG2-RM26. Conclusions These findings demonstrate the effectiveness of the IEDDA click reaction for fluorine-18 labelling of GRPR-targeting PET tracers. Future studies should focus on increasing the hydrophilicity of the imaging probe to improve the targeting properties and biodistribution profile of the radioligand.